Characterization of Blood Donor Defferal at Blood Donation Unit Indonesian Red Cross Bojonegoro - Nina Difla Muflikhah (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2022)
Availability of safe blood and blood products is a critical component in improving adequate blood supply and blood products. Blood donation collected from 1% of the population is usually the minimum requirement to meet a country’s most basic need for blood. Blood product declare as a life saving product which treat diseases and maintains health. Safety blood donor plays a vital role for donor and recipient. Recruiting donor should follow criterias during blood selection. This study aimed to analysis of blood donor referral in blood donation unit of Bojonegoro following some characteristics such as hemoglobin levels, blood pressure, and consumption. This study was conducted by reviewing the deferral donor records during June to July 2022 at Blood Donation Units Bojonegoro. Out of the 668 screened prospective donors, 117 (17%) were deferred. Hemoglobin levels was the major (90% from 117) cause of temporary deferral as well as the second cause of overall deferrals. Blood pressure and latest consumption time constituted 9% and 1% of the deferral cases, respectively. From 117 deferred donor, deferral rate among male donors was 53% (62 donor). Among female donors, it was 47% (55 donor). Thus, the prevalence of deferral was significantly higher among female donors than among male donors. Out of the 668 screened prospective donors, 117 (17%) were deferred. Hemoglobin levels was the major (90% from 117) cause of temporary deferral as well as the second cause of overall deferrals. Blood pressure and latest consumtion time constituted 9% and 1% of the deferral cases, respectively Keywords: Blood Donor, Defferals, Blood Bank